2004
DOI: 10.1246/cl.2004.492
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of the Structure of Alkyl Monolayers on Si(111) Surface via Si–C Bond by ATR-FT-IR Spectroscopy

Abstract: The temperature dependence of C–H stretching modes of alkyl monolayer formed on Si(111) surface was investigated by an attenuated total reflection Fourier transform infrared spectroscopy from room temperature up to 540 K. Continuous disordering of the monolayer was indicated from the gradual peak shifts toward higher frequency in C–H stretch modes upon heating. The irreversible conformational disorder was introduced in the monolayer above 440 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Only at 1500 K, there is some correlation between the percentage of carbon and the chain length (except for the C3 layer), whereas at the highest temperatures, the C3 layer is the most stable, even more than the C10 layer. This is in agreement with experimental results in which no correlation with the alkyl chain length was observed . As we discussed above, the high stability of the C3 monolayer is due to the presence of stable bicoordinated Si–CH 2 CH 2 CH 2 –Si moieties (Figure a).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Only at 1500 K, there is some correlation between the percentage of carbon and the chain length (except for the C3 layer), whereas at the highest temperatures, the C3 layer is the most stable, even more than the C10 layer. This is in agreement with experimental results in which no correlation with the alkyl chain length was observed . As we discussed above, the high stability of the C3 monolayer is due to the presence of stable bicoordinated Si–CH 2 CH 2 CH 2 –Si moieties (Figure a).…”
Section: Resultssupporting
confidence: 92%
“…An irreversible conformational disorder was observed for a C18 monolayer above 440 K; however, the length of the alkyl chain was not found to affect the desorption temperature, except for the short C2 chain, which was reported to be more stable . The appearance of a vibrational mode characteristic of the Si–CH 3 group has led to the conclusion that a secondary desorption mechanism could be operative at high temperatures for long alkyl chains according to as a consequence of the breakage of C–C bonds of the alkyl chain. , However, surface Si–CH 3 groups were also detected during the decomposition of a C2 layer, and it was proposed to proceed according to Methylated surfaces have no SiH groups because the methyl group is atop all surface Si atoms with the covalent Si–C bond oriented normal to the surface. , Its thermal stability is higher than for longer alkyl chains, , and at high temperatures, the formation of silicon carbide was observed. , The superior stability of the methylated silicon surface has been attributed to the fact that the β-desorption mechanism (eq ) is not operative for methyl.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the commonly accepted thermal hydrosilylation mechanism requires the heating of the hydrogenated silicon surface at temperatures ranging from 150 to 200 °C to homolytically cleave the Si–H bonds to form silyl radicals, which subsequently react with alkenes or alkynes. , As mentioned in Section , the thermal stability experiments reported in the literature are performed in the temperature range of 200–500 °C. Therefore, at these temperatures, the surface will be populated by silyl groups produced by the rupture of Si–H and/or Si–C bonds. These observations further support the fact that the decomposition of the monolayers occurs according to reaction rather than reaction as predicted by the ReaxFF simulations.…”
Section: Results and Discussionmentioning
confidence: 99%
“…At higher temperature, the signals of characteristic modes decrease, while the Si–H vibrational modes appear simultaneously. From this observation, they concluded that the grafted layer desorbs according to a β-hydride elimination reaction For long alkyl monolayers, Yamada et al observed a loss in the ν CH intensity after annealing above 217 °C together with a small shift of the ν CH bands, which they attributed to an irreversible loss in the organization of the layer . Faucheux et al investigated the thermal stability under oxidizing or reducing atmospheres using IR spectroscopy and found that the layers are thermally stable up to 250 °C .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation